1992
DOI: 10.1111/j.1349-7006.1992.tb02758.x
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Effects of Fungal and Herb Metabolites on Azoxymethane‐induced Intestinal Carcinogenesis in Rats

Abstract: Modifying effects of a fungal product, flavoglaucin, and four plant‐derived chemicals, shikonin, gingerol, oleanolic acid and paeoniflorin, on intestinal carcinogenesis were examined in a rat model using azoxymethane (AOM). A total of 280 male F344 rats, 6 weeks old, were divided into 12 groups. Group 1 (30 rats) was given two subcutaneous injections of 15 mg/kg of AOM at the start of the experiment. Groups 2 (30 rats), 3 (20 rats), 4 (20 rats), 5 (30 rats) and 6 (30 rats) received a test chemical (flavoglauci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 24 publications
3
47
0
1
Order By: Relevance
“…Our observation, that the inhibition of proliferation induced by triterpenes in astrocytoma cell lines is mediated via apoptosis, is consistent with earlier reports that show how these active triterpenes produce a wide variety of inhibitory effects on tumor promotion (21)(22)(23)(24)28), as well as antiproliferative and proapoptotic effects on human cancer cells of different lineage such as leukemia, mamarian and colon adenocarcinoma, or melanoma cells (25,(29)(30)(31)(32)(33). However, the precise biochemical basis of these antitumor activities remains to be determined.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observation, that the inhibition of proliferation induced by triterpenes in astrocytoma cell lines is mediated via apoptosis, is consistent with earlier reports that show how these active triterpenes produce a wide variety of inhibitory effects on tumor promotion (21)(22)(23)(24)28), as well as antiproliferative and proapoptotic effects on human cancer cells of different lineage such as leukemia, mamarian and colon adenocarcinoma, or melanoma cells (25,(29)(30)(31)(32)(33). However, the precise biochemical basis of these antitumor activities remains to be determined.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, the potential therapeutic significance of this olive subproduct has not yet been completely studied. It has been reported that oleanolic acid produces a wide variety of excellent antitumorpromoting activity in the in vivo carcinogenesis test, including decrease of the incidence of induced intestinal tumor in a rat model (21), inhibition of angiogenesis, which is important for the progressive growth of solid tumors (22), tumor promotion (23), and implanted tumor growth in mice (24). However, in spite of these pleiotropic effects, the exact mechanisms by which natural oleananes promote such cellular outcomes are not well understood and the biochemical basis of these actions remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Half inhibitory concentration, IC 50 , is a widely used parameter for the comparison of pharmacological activities of compounds with inhibitory functions. Shikonin was reported to inhibit phorbol 12-myristate 13-acetateinduced superoxide generation in neutrophils at an IC 50 of 2.0 μm (Yoshimi et al, 1992), and to inhibit leukotriene B4 synthesis at an IC 50 of 0.62 μm (Wang et al, 1994). Shikonin also reacts directly with reactive oxygen species including singlet oxygens, superoxides and hydoxy radicals at an IC 50 of 9.0 μm (Gao et al, 2000), and selectively blocks the binding of chemokines, CCL5 and CCL4, to their receptors on monocytes with an IC 50 of 3.6 μm and 2.8 μm, respectively (Chen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…8) It has also been demonstrated that the administration of shikonin reduces the volume of intestinal neoplasms induced by azoxymethane. 9) Recently, shikonin has been shown to induce apoptosis in several human tumors. The treatment of HL-60, 10) HeLa, 11) bladder carcinoma cells, 12) and melanoma cells 13) with shikonin induced apoptosis through increased caspase-3 activity.…”
mentioning
confidence: 99%